18F FDG imaging – response criteria in tumors. Issue 147 (February 2022) - Guglielmi, Riccardo; Andreisek, Gustav; Halpern, Benjamin S.
Highlights: 18 F-FDG PET/CT plays an important role in treatment response assessment and prognostic evaluation in patients with cancer. Standardized molecular imaging allows for higher sensitivity in tumor detection and most often enables detection even below pathologic size thresholds on CT. Various hybrid imaging evaluation criteria have been proposed for standardization of therapy response. Abstract: With the progress of medical oncology, it became apparent that anatomical imaging is oftentimes insufficient for therapy response evaluation. Hybrid imaging, namely 18 F-FDG PET/CT has helped to overcome these limitations. The aim of this paper is to emphasize the utility and impact in clinical use of 18 F-FDG PET/CT, and to give an overview of the most important 18 F-FDG PET/CT tumor response criteria. We also focus on standardization of hybrid imaging techniques as this is of outmost importance to provide reliable imaging evaluation.